Exotic Spintronic Properties of Transition‐Metal Monolayers on Graphyne. Issue 2 (9th November 2021) - Ren, Xiaoxiong; Huang, Junsheng; Li, Ping; Zhang, Yun; Guo, Zhi‐Xin
Abstract: The recent discovery of 2D magnetic materials, which are compounds of transition metals (TM) with other elements, has opened new avenues for basic research on low‐dimensional magnetism and potential applications in spintronics. To further explore new 2D magnets of pure TM is an interesting topic. Based on the first‐principles calculations, here a strategy of obtaining monolayer TM magnets, i.e., depositing TM atoms on graphyne (Gy), which has proper hexagonal hollow geometry, is proposed. It is found that a TM monolayer with perfect hexagonal geometry can be formed on Gy. The TM monolayer exhibits a wealth of physical properties in dependence of TM species, such as ferromagnetic and anti‐ferromagnetic ground states, as well as intriguing semimetal and half‐metal characteristics. It is also found that the half‐metal characteristics make the monolayer TM have great potential applications in horizontal magnetic tunnel junction (MTJ) devices, where the tunneling magnetoresistance can reach as high as 850 000%. These results provide a new framework for obtaining 2D magnets with outstanding spintronic properties. Abstract : A new method of growing a single‐layer transition metal magnetic film is proposed, i.e., depositing transition metal atoms on graphyne, which has proper hexagonal hollow geometry. The magnetic film exhibits a wealth of physical properties in dependence of transition metal species, having great potential applications in the horizontal magnetic tunnel junction devices.